Focal psychodynamic therapy, cognitive behaviour therapy, and optimised treatment as usual in female outpatients with anorexia nervosa (ANTOP study): 5-year follow-up of a randomised controlled trial in Germany. (April 2022) - Herzog, Wolfgang; Wild, Beate; Giel, Katrin E; Junne, Florian; Friederich, Hans-Christoph; Resmark, Gaby; Teufel, Martin; Schellberg, Dieter; de Zwaan, Martina; Dinkel, Andreas; Herpertz, Stephan; Burgmer, Markus; et al.
Summary: Background: Anorexia nervosa is a serious illness leading to substantial morbidity and mortality. The Anorexia Nervosa Treatment of Outpatients (ANTOP) study is the largest randomised controlled trial (RCT) globally that uses psychotherapy in outpatients with anorexia nervosa. In this Article, we report the results of the 5-year follow-up. Methods: The ANTOP study is an open-label, multicentre RCT involving 242 adult female outpatients with anorexia nervosa. Participants were recruited from ten university hospitals in Germany, had to be aged at least 18 years and female, and have a diagnosis of anorexia nervosa with a body-mass index (BMI) of 15·0–18·5 kg/m 2 . Participants were randomly allocated (1:1:1) to 10 months of treatment with focal psychodynamic therapy, enhanced cognitive behaviour therapy, or optimised treatment as usual; complete masking of the participants was not possible. The mean duration of the follow-up was 5·96 years (SD 0·2) after randomisation. The primary outcome was change in BMI from baseline at the end of treatment; here, we present the change in BMI from baseline to the 5-year follow-up, using an intention-to-treat approach with a mixed model for repeated measurements. Groups were also compared according to global outcome (based on the combination of BMI and measures of anorexia severity), eating pathology (based on the Eating Disorder Inventory 2), and other secondary mental health outcomes. We did a linear regression analysis to identify the predictors of BMI at follow-up. Findings: Between May, 2007, and June, 2009, we screened 727 patients for eligibility; at baseline, 242 patients with a mean BMI of 16·7 kg/m 2 (SD 1·0) were included and randomly allocated to 10 months of treatment with focal psychodynamic therapy, enhanced cognitive behaviour therapy, or optimised treatment as usual. 154 (64%) of 242 patients completed the 5-year follow-up assessment (53 [66%] of 80 in the focal psychodynamic therapy group, 55 [69%] of 80 in the enhanced cognitive behaviour therapy group, and 46 [56%] of 82 in the optimised treatment-as-usual group), with a mean age of 32·4 years; all reported their ethnicity as White. At the 5-year follow-up, there was an improvement in mean BMI, eating pathology, and global outcome in all treatment groups with no significant differences between treatment groups. Estimated mean BMI was: 18·64 kg/m 2 (95% CI 18·07–19·21) in the focal psychodynamic therapy group (with an estimated mean BMI gain from baseline to 5-year follow-up of 1·91 kg/m 2 [1·34–2·48]); 18·70 kg/m 2 (18·15–19·25) in the enhanced cognitive behaviour therapy group (with an estimated mean BMI gain of 1·98 kg/m 2 [1·43–2·53]); and 18·99 kg/m 2 (18·39–19·59) in the optimised treatment-as-usual group (with an estimated mean BMI gain of 2·26 kg/m 2 [1·67–2·86]). There were no significant differences between treatment groups regarding BMI at the 5-year follow-up; the estimated difference was –0·06 (−0·85 to 0·73) between the focal psychodynamic therapy and enhanced cognitive behaviour therapy groups; –0·35 (−1·18 to 0·47) between the focal psychodynamic therapy and optimised treatment-as-usual groups; and –0·29 (−1·10 to 0·52) between the enhanced cognitive behaviour therapy and optimised treatment-as-usual groups. On the basis of observed data, global outcome at the 5-year follow-up showed 41% (33–49) full recoveries, 41% (33–49) partial recoveries, and 18% (12–24) with full-syndrome anorexia nervosa. One patient initially treated in the enhanced cognitive behaviour therapy group died by suicide between the 1-year and 5-year follow-up. BMI at the 5-year follow-up was predicted by BMI at baseline (p=0·0021), illness duration (p=0·0004), and depression at baseline (p=0·012). Interpretation: The long-term results of the ANTOP trial confirm the improvement in BMI of patients with anorexia nervosa in all groups; however, a substantial proportion of patients had a poor global outcome. The predictors for the long-term course of anorexia nervosa in our ANTOP study show that we need to treat patients with anorexia nervosa at an earlier stage of the disease, with a clear focus on weight gain and considering other comorbidities (especially depression). Funding: German Federal Ministry of Education and Research.